Reventing brittle hybrid high-strength reinforced concrete slab collapse due to punching shear using coal flyash substitution, tie wire fiber and polypropylene fiber. Issue 1 (February 2021) - Aulia, T B; Hayati, Y; Idris, Y; Amalia, Z; Handoko, E
Abstract: Heavy vehicles crossing a bridge could lead in punching shear failure at reinforced concrete deck slab due to highly concentrated axial compressive load from their wheels. This may occur in a very brittle manner and difficult to fix. Effort in improving punching shear capacity of deck slab is with using high-strength concrete and adding fibers into concrete. However, high-strength concretes are not environmentally friendly because using a lot of cement contributing to large CO2 emissions to the atmosphere during its production, therefore coal flyash is used as a part of cement substitution. Based on these facts, this research aims to analyze punching shear capacity of hybrid high-strength reinforced concrete slabs using coal flyash as cement substitution which added with tie wire fiber and polypropylene fiber. The amount of coal flyash was taken 15% from cement weight as cement substitution, tie wire fiber 2% from concrete volume having aspect ratio l/d of 40 and straight shaped fiber geometry, as well as polypropylene fiber 0.2% from concrete volume. Three hybrid high-strength reinforced concrete slabs of 60 × 60 cm 2 (two-way-slab) with a thickness 12 cm, w/c-ratio of 0.30 and concrete cylinder compressive strength of f′c = 60 MPa were made with 15% coal flyash and 2% tie wire fiber (CFA-TWF), 15% coal flyash and 0.2% polypropylene fiber (CFA-PPF), as well as 15% coal flyash and combination of 2% tie wire fiber and 0.2% polypropylene fiber (CFA-TWF-PPF). One plain slab without flyash and fibers (PSHSC) was tested as a comparison. To guarantee the punching shear failure mechanism, the slabs were reinforced with tensile reinforcement of 10 Ø 10.5 mm which was distributed to each direction and tested then by giving a concentrated punching load. The results showed that using of coal flyash substitution and addition of fibers could significantly increase the punching shear capacity and structural ductility of hybrid high-strength concrete slabs with the highest enhance both achieved in CFA-TWF-PPF, i.e., 67.91% for punching shear capacity and 92.82% for structural ductility compared with plain slab PSHSC.